Possible NMDA antagonist properties of drugs that affect high pressure neurological syndrome. - Shuker, M. A. (1994)
1. Previous studies have suggested that a series of drugs modelled on part of the strychnine molecule interfere with the development of high pressure neurological syndrome (HPNS) and it was presumed that this effect was via an action on inhibitory glycinergic transmission. We have now used the rat hippocampal slice preparation to examine the possibility that some of these drugs might instead have an action at the strychnine-insensitive (SI) glycine binding site associated with the NMDA receptor. 2. D-2-Amino-5-phosphonovalerate (AP5) and 7-chlorokynurenate (7CK) had no significant effect on the height of the population spike recorded from the CA1 region in 1 mM Mg2+ medium, but both blocked the multiple population spikes recorded in Mg(2+)-free medium. The effect of 7CK, but not AP5, was reversed by 200 microM D-serine which is consistent with the known antagonist action of 7CK at the SI-glycine site. 3. A derivative of benzimidazole, which shows the clearest structural similarities to known SI-glycine site antagonists and ameliorates HPNS, mirrored the effects of 7CK although it was considerably less potent. 4. Gramine, which exacerbates HPNS, significantly increased the number of population spikes evoked in Mg(2+)-free medium. 5. Mephenesin, which is the most potent known drug in ameliorating HPNS, had no significant effect on the response recorded in 1 mM Mg2+ and significantly reduced the number of population spikes recorded in Mg(2+)-free medium, but this effect was only partially reversed by the addition of D-serine. 6. The results are consistent with the benzimidazole derivative, but not gramine, being an antagonist at the SI-glycine receptor.(ABSTRACT TRUNCATED AT 250 WORDS)